Life experiences of Roma women: a collaborative approach to their study - Hernández, Liria; Gay y Blasco, Paloma (Romano džaniben, 2018)
This article outlines some of the challenges, in terms of academic practices, for a feminist approach to the experiences of Roma women. The authors examine their friendship and scholarly collaboration as two women from very different backgrounds, Roma and non-Roma. In this endeavour they openly acknowledge the advantages and also the drawbacks and limits of such cooperation. They reflect on their intertwined life stories, and on their experiences of working together whilst standing on different sides of academic and ethnic divides. From this dual standpoint they ask how Roma women should be represented in scholarly texts, by whom, and using what kinds of terms and approaches. They propose their collaboration – its limits as much as its successes – as a thinking tool and experiment that might encourage both debate and collaboration.